Os critérios de investimento utilizados pelos investidores anjo no Brasil: uma análise sobre suas priorizações - Amorim, Ronaldo Alves de (2016)
Startups, young firms generally developing an innovative proposal and under extreme uncertainty conditions, generally need external funds to grow and these new enterprises frequently turn to angel investors as an option of venture capital. It happens because startups are young companies with no financial record and most of the times without real asset to be given as collateral, therefore, with not enough credentials to apply for a conventional bank financing. Angel investors are wealthy individuals who invest not just own money, but also their expertise and knowledge in startups, also known as ventures. The objective of this research is to better comprehend the angel investment decision making process, identifying and analyzing the most important criteria that Brazilian angel investors use to decide on funding new ventures. The main research environment is Gávea Angels, the first angel association in Brazil, and on a secondary basis, investors from this researcher and his professor networking. This research is quantitative and based on a questionnaire with attributes previously defined in research performed in the USA with answers varying from 1 (not important) up to 5 (very important). The result of criteria prioritization was based on simple average followed by their standard deviation. It also compared and analyzed empirical results of this research with the findings of another relevant search conducted in the USA by Sudek (2006). Answers were based in past experiences lived by each investor and results were analyzed not just in an aggregate way but also segregated by investors seniority (given by number of investments done). This research also analyzed the most important behavioral criteria of management team. Confirming findings of other international studies, the results of this research showed that irrespective of the market, product or financial criteria, the criterion prioritized were those regarding entrepreneur and his/her management team, as it follows: (1) trustworthiness/honesty of the entrepreneur; (2) enthusiasm/commitment of the entrepreneur; (3) management team; (4) domain expertise of the entrepreneur. The criterion ‘how persistence they will be without giving up’ and ‘passion of the team’ were the most important attributes on the particular analysis of ‘management team’. The contribution of this work is to stimulate more studies of a very incipient issue in the world and mainly in Brazil, and also increase the understanding about investing in startups, bringing more insights to entrepreneurs of what matters most to investors when searching for venture capital, and also shedding light to the positive impact of this market on Brazilian economy development.